Progressive generalized motor absence seizures. Regarding a clinical case - Hernández Navas, Jorge Andrés (2026)
Progressive generalized motor absence seizures represent an unusual and severe variant of absence seizures, characterized by brief episodes of loss of consciousness accompanied by motor manifestations such as myoclonus or automatisms, which progressively worsen over time. In the context of the patient’s clinical case, who has shown an evolution from absence seizures to generalized tonic-clonic seizures, this spike-wave activity could suggest an imbalance in inhibitory and excitatory activity within the involved neural networks. The progression to tonic-clonic seizures may be associated with the propagation of epileptiform activity beyond the primary cortical areas, implicating additional cortical networks that could be related to the generation of motor activity. This aligns with the theory that the progression of seizures might involve a broader recruitment of the cortex, potentially explaining the emergence of more severe symptoms. In conclusion, the interpretation of this EEG and the correlation with clinical findings suggest a complexity in the presentation of epilepsy in this patient, highlighting the importance of comprehensive and personalized management. The evolution and response to treatment should be carefully monitored to adjust therapeutic strategies according to the progression of the disease.